Effect of haemoglobin levels on outcome in intravenous thrombolysis-treated stroke patients. (June 2020) - Altersberger, Valerian L; Kellert, Lars; Al Sultan, Abdulaziz S; Martinez-Majander, Nicolas; Hametner, Christian; Eskandari, Ashraf; Heldner, Mirjam R; van den Berg, Sophie A; Zini, Andrea; Padjen, Visnja; Kägi, Georg; Pezzini, Alessandro; et al.
Introduction: Alterations in haemoglobin levels are frequent in stroke patients. The prognostic meaning of anaemia and polyglobulia on outcomes in patients treated with intravenous thrombolysis is ambiguous. Patients and methods: In this prospective multicentre, intravenous thrombolysis register-based study, we compared haemoglobin levels on hospital admission with three-month poor outcome (modified Rankin Scale 3–6), mortality and symptomatic intracranial haemorrhage (European Cooperative Acute Stroke Study II-criteria (ECASS-II-criteria)). Haemoglobin level was used as continuous and categorical variable distinguishing anaemia (female: <12 g/dl; male: <13 g/dl) and polyglobulia (female: >15.5 g/dl; male: >17 g/dl). Anaemia was subdivided into mild and moderate/severe (female/male: <11 g/dl). Normal haemoglobin level (female: 12.0–15.5 g/dl, male: 13.0–17.0 g/dl) served as reference group. Unadjusted and adjusted odds ratios with 95% confidence intervals were calculated with logistic regression models. Results: Among 6866 intravenous thrombolysis-treated stroke patients, 5448 (79.3%) had normal haemoglobin level, 1232 (17.9%) anaemia – of those 903 (13.2%) had mild and 329 (4.8%) moderate/severe anaemia – and 186 (2.7%) polyglobulia. Anaemia was associated with poor outcome (ORadjusted 1.25 (1.05–1.48)) and mortality (ORadjusted 1.58 (1.27–1.95)). In anaemia subgroups, both mild and moderate/severe anaemia independently predicted poor outcome (ORadjusted 1.29 (1.07–1.55) and 1.48 (1.09–2.02)) and mortality (ORadjusted 1.45 (1.15–1.84) and ORadjusted 2.00 (1.46–2.75)). Each haemoglobin level decrease by 1 g/dl independently increased the risk of poor outcome (ORadjusted 1.07 (1.02–1.11)) and mortality (ORadjusted 1.08 (1.02–1.15)). Anaemia was not associated with occurrence of symptomatic intracranial haemorrhage. Polyglobulia did not change any outcome. Discussion: The more severe the anaemia, the higher the probability of poor outcome and death. Severe anaemia might be a target for interventions in hyperacute stroke. Conclusion: Anaemia on admission, but not polyglobulia, is a strong and independent predictor of poor outcome and mortality in intravenous thrombolysis-treated stroke patients.